Dr. Martin Luther King, Jr.'s Legacy: An Economic Justice Imperative - Susan R. Jones (Washington University Journal of Law & Policy, 2005)
In this Essay, I will explore the ways in which Dr. King’s legacy demands that lawyers work to abolish poverty and homelessness and the ways that lawyers can help to advance economic opportunity for low-income people. I will do this by discussing legislation that promotes the abolition of poverty and the ways in which nonprofit groups and progressive corporations can support the cause.
Keywords: Public interest; Lawyers; Poverty; King; Martin Luther; Jr.; 1929-1968